NEW MODELS FOR A SINGLE-MANUFACTURER MULTI-RETAILER SUPPLY CHAIN UNDER VENDOR MANAGED INVENTORY PROGRAM - Parsa, Mostafa; Mollaverdi-Esfahani, Naser; Alinaghian, Mehdi; Rezvan, Mohammad Taghi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
Vendor managed inventory (VMI) is a partnership between a supplier and buyers whereby supplier makes inventory replenishment decisions on behalf of buyers. A (z, Z) VMI contract is one of the strategies that protects the buyers from dispatching a lot of inventory by the supplier using lower bound z and upper bound Z on the buyer’s inventory level. This paper develops a model for a single vendor and multiple retailers supply chain under (z, Z) VMI contracts by considering the time value of money and also introduces a novel approach designated as “secondary negotiations” in order to improve manufacturer’s cost or retailers’ profits. Numerical analysis is designed to compare the performance (z, Z) VMI contract and independent system (without VMI) that both consider the time value of money. Furthermore, computational results shows that secondary negotiation how change in both upper bounds and replenishment quantity and cause to absorb and keep important retailers and increase their level of satisfaction for developing more mutual cooperation.